Går grænsen ved 'Hej Hitler'? Sort Mælk - Holocaust i ny kunst - Gutman, Natalia (Rambam. Tidsskrift for jødisk kultur og forskning, 2014)
Black Milk - Holocaust in Contemporary Art A concentration camp built from Lego, a gold brooch with the inscription Jude, and a pile of bleeding trunks were some of the works that could be seen at the exhibition Black Milk – Holocaust in contemporary art at the Museum of Contemporary Art in Roskilde in the spring of 2014. Works by thirteen international artists from Bolivia, Denmark, Israel, Poland, South Africa, and the United States were gathered to show how artists from around the world are continuously interested in processing Holocaust artistically. The artists’ personal perspectives and different cultural backgrounds formed a complex exhibition of works that were both confrontational, poetic, and provocative. The selected artists were all second and third generation after the Holocaust; some Jewish and others non-Jewish. The exhibition was met with great interest from media and audience. Dealing with the Holocaust can be complicated. It is a sensitive subject, casting shadows all the way into the 21st century. The exhibition was therefore subject to many considerations, both artistically, professionally, practically, and ethically. In particular, finding the right title for the exhibition proved that the topic is still a very sensitive one which requires thought and consideration. Is ’Hi, Hitler’ too provocative? This and other questions and experiences regarding the exhibition are dealt with by the curator Natalia Gutman.